The influence of immune checkpoint blockade on the outcomes of allogeneic hematopoietic stem cell transplantation - Hu, Yalei; Wang, Yuxin; Min, Kaili; Zhou, Huisheng; Gao, Xiaoning (Frontiers in Immunology, 2024)
The principle of immune checkpoint blockade therapy is based on the activation of T cells. Immune checkpoint inhibitors (ICIs), such as anti-PD-1/PD-L1 and anti-CTLA-4 antibodies, have demonstrated effectiveness in treating solid tumors by reinvigorating the immune system to recognize and eliminate malignant cells. In recent years, ICIs have shown promise in certain patients with relapsed or refractory lymphoma and myeloid malignancies. Allogeneic hematopoietic stem cell transplant (allo-HCT) currently remains the only curative immunotherapy option for eligible patients with these hematologic malignancies. An increasing number of patients with indications for allo-HCT have received treatment with ICIs either before the procedure or as a therapy for relapse after allo-HCT. Nevertheless, initial reports suggest that patients exposed to immune checkpoint inhibitors either before or after allo-HCT are at an increased risk of developing severe graft-versus-host disease and other immune-related adverse events, likely due to the persistent effects of immune checkpoint blocking. Maximizing therapeutic benefits while minimizing side effects of the combination of checkpoint blockade immunotherapy and allo-HCT is an active area of research aimed at improving the prognosis of relapsed or refractory hematologic malignancies. However, there is still a lack of rational design strategies to optimize the combined use of these two different types of immunotherapies. In this review, we addressed the scientific rationale behind ICIs for treating lymphoma and myeloid malignancies. We also summarized the evidence supporting the use of ICIs as salvage therapy before and after allo-HCT. Additionally, we offered insights into current approaches for preventing and treating graft-versus-host disease and other immune-related adverse events during the procedure.